Learning English Using Narative Text at Junior High School - Wildan Fakhri Rosyadi; Achmat Dony Septyan; Wahyu Indah Mala Rohmana (Pendidikan Bahasa Inggris Universitas Nurul Huda, 2023)
This article discusses of the teacher's ways and methods of teaching narrative text in English classes at the junior high school level. Learning English is not a prioritized language of communication, so learning literature is one of the teacher's problems in the classroom. Therefore, this article aims to find out the problems using narrative text and solutions to overcome them. The method used in this study was descriptive qualitative through interviews with a teacher at SMPN 1 Kedunggalar. The results of the research indicated that the most obvious problem of using narrative text was the lack of students' understanding in several aspects such as: the meaning of vocabulary, sentences, and delivery during the lesson. Even though there are some problems faced by students, they will later gain knowledge of language both linguistics and introduction to new cultures when learning English using narrative text. This is all thanks to the teacher trying to create an interactive classroom atmosphere so that literature and language learning can be conveyed and well received.